Question #bb2ac

1 Answer
Feb 7, 2018

sinx+xcosx+sec^2xsinx+xcosx+sec2x

Explanation:

The first term of the derivative can be simplified to xsinxxsinx. This is why you spend all those agonizing hours doing trig identities!

xtanx/secx = (xsinx/cosx)/(1/cosx) = xsinx/cosx*cosx=xsinxxtanxsecx=xsinxcosx1cosx=xsinxcosxcosx=xsinx

So now your function looks like this:

xsinx+tanxxsinx+tanx

Take the derivative of each term separately, using the product rule for the first term.

(sinx +xcosx)+sec^2x(sinx+xcosx)+sec2x